Calling out to the Faraway: Accessing History through Public Gestures in Howrah, West Bengal - Atreyee Majumder (South Asia Multidisciplinary Academic Journal)
This article narrates events, performances and gestures from public life on the rural-urban corridors of Howrah District, on the west bank of the river Hooghly, in southern West Bengal. Howrah is a place of decadent industrial activity, owing much of its spatial organization to colonial manufacture and trade on the edges of the colonial capital of Calcutta. Public figures in Howrah attempt to lift a place and an associated public out of its current political and historical anonymity. Each uses public gesture to appropriate distant phenomena, quite far-fetched and tenuously linked to their immediate existence. Such public gesture emerges as a key tool for gaining historical luminosity. Their words, gestures and stances are used to access history and historical significance, linking the historical charge of distant entities to immediate worlds, and aiding access to larger scale in space and time.